Restorative Justice in Islamic Criminal Law: A Comparative Study of Diyat and Modern Victimology - Muhammad Jaelani; Fadhli Muhaimin Ishaq; Muhammad Yusuf (Jurnal El-Thawalib, 2026)
Contemporary criminal justice systems, largely influenced by retributive penal theory, have been criticized for their limited capacity to address victims’ interests. Indonesian positive law, including Law No. 31 of 2014 on the Protection of Witnesses and Victims and Law No. 20 of 2025 on Criminal Procedure Law, also continues to exhibit normative gaps in victim-centered justice mechanisms. This article examines diyat in fiqh jinayah as an instrument of restorative justice and analyzes its contribution to the development of Islamic victimology within contemporary criminal law. This study employs normative legal research using statutory, conceptual, and comparative approaches. Primary legal sources consist of the Qur’an, Hadith, and classical fiqh jinayah literature, while secondary sources include legislation, international legal instruments, books, and scholarly journal articles. Data were collected through library research and analyzed using qualitative descriptive and comparative methods. The study identifies four major contributions of diyat to contemporary victimology. First, diyat provides structural compensation guarantees through the institution of ‘aqilah, which distributes financial responsibility collectively. Second, it recognizes victim autonomy as a juridical right through haqq al-adami, granting determinative authority to victims or their legal heirs. Third, the mechanism of ‘afw (forgiveness) incorporates moral and relational restoration beyond conventional restitution. Fourth, diyat institutionalizes community participation through ‘aqilah and ‘asabiyyah (social solidarity). These principles constitute a coherent framework of Islamic victimology compatible with universal restorative justice principles and relevant to Indonesia’s criminal justice reform.